População em situação de rua e o seu processo saúde-doença-cuidado - Sousa, Samyla Fernades de (2023)
The Homeless Population suffers from extreme poverty, insecurity, exposure to risks and are denied their status as human beings. They suffer from lack of physical and emotional well-being, showing vulnerability to infectious, chronic, and psychiatric diseases, among others. Although the Homeless Population has the right to access health services, the access becomes limited by prejudice, undue impositions, and high demand of users. Facing these barriers, the Homeless Population is creating new forms of care that are not only linked to public health policies, but that involve other public policies, informal and popular resources and the context of their relationships on the streets. Thus, the research aims to understand the health-illness-care process experienced by the homeless population and, as specific objectives, to understand the meanings of health, disease, and care in the perspective of homeless people, to describe the impact of the COVID-19 pandemic on the health-illness-care process of this group, and to identify the health care practices developed by them. To achieve the purposes we used a qualitative method, conducting semi-structured interviews. The research took place in the Centro Pop Center of Fortaleza-CE, which participated in this research 7 participants who lived on the streets for at least 1 year, and were assisted or accompanied by the mentioned social equipment. The participants were named with fictitious names. The corpus of the research was composed by the transcription of the audio recorded interviews and the data analysis used the thematic content analysis with the support of the Atlas T.I. software. The results and analysis pointed out that the living conditions of the participants are circumscribed to numerous difficulties and social relations marked by prejudice, devaluation, and stigmatization. The homeless population suffers from unhealthy conditions and lacks access to basic needs, showing all the suffering of their experiences. The pandemic of COVID-19 crossed the lives of these people in a challenging way, making their living conditions even more difficult. We noticed that there is no uniformity of well-defined meanings of health-illness, when considered from the point of view of these participants. Their health-illness-care processes are involved in their life contexts, their subjectivities, and are also related to socioeconomic, political, environmental, and cultural issues that influence this process. Regarding care, it is perceptible the support networks in the care of this group and how they acquired strategies for self-care according to their life contexts. Thinking about health, as it iscurrently conceptualized from a broad perspective, distances itself from the living conditions of the homeless population, which deserve more public policies and actions based on their life contexts and that treat with dignity their issues in their healthdisease-care processes so that they have health and life quality.